TEACHING SPEAKING BY USING TALKING STICK TECHNIQUE FOR SENIOR HIGH SCHOOL STUDENTS - Ajeng Novia Anggraini; Fitrawati Fitrawati (Universitas Negeri Padang, 2016)
Speaking is one of the four elements of language that is very important to master in order to support a person's ability to speak. Talking is the process of conveying an idea and information orally to the opponent. In Indonesia, English has been taught since Elementary level up to University level. However, not many students are able to speak English fluently. This paper is discussing about one technique that can help teacher in teaching speaking in more enjoyable way at classroom. The technique that will be discussed is Talking Stick Technique. The technique uses a wooden stick as a sign for whom who may speak.